Persepsi Guru dan Siswa terhadap Implementasi Kurikulum 2013 dalam Mata Pelajaran Sejarah di SMA Negeri 5 Merangin - Sinta Wulandari, Nur Agustiningsih (Universitas Batanghari Jambi, 2018)
Abstract The implementation of the 2013 curriculum that is enacted by the government is determined by the perceptions of the teachers, where this perception is rooted in the teacher's own knowledge and experience. From the perspective of students, curriculum changes certainly have an impact on individual perceptions. The new Merangin High School 5 N 5 uses the 2013 curriculum, found differences in perceptions between history subject teachers and students in schools regarding the 2013 curriculum. Therefore, this research needs to be done considering that each individual (teacher and student) has a different way of addressing and interpreting the 2013 curriculum is in accordance with their knowledge, experience and belief system. This research was conducted at SMA N 5 Merangin, involving a sample of 2 history subject teachers and 71 students selected through purposive sampling and snowball sampling techniques. Data collection in this study uses data triangulation techniques including; questionnaire techniques, structured interview techniques, and documentation techniques. The data obtained are then analyzed by interactive model analysis techniques. The results showed from the teacher's perspective, the two subjects interviewed had perceptions of changes in the 2013 curriculum only limited to technical assessment and learning orientation, but did not fully understand the foundation of the 2013 curriculum such as the formulation of graduate competencies. This is because there is a